Operations management : - Heizer, Jay (Pearson, 2017)
Operations management: Sustainability and supply chain management presents a broad introduction to the field of operations in a realistic and practical manner, while offering the largest and most diverse collection of issues on the market. Problems found contain ample support–found in the book’s solved-problems and worked examples–to help readers better understand concepts important to today’s operations management professionals.